2020
DOI: 10.1039/c9ra08741a
|View full text |Cite
|
Sign up to set email alerts
|

Development of Prosopis juliflora carbon-reinforced PET bottle waste-based epoxy-blended bio-phenolic benzoxazine composites for advanced applications

Abstract: Schematic representation of development of functionalised Prosopis juliflora carbon (f-PJC) reinforced PET-epoxy resin (PETEP) blended bio-phenolic (cardanol) based benzoxazine (CBz) hybrid composites for high performance applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 66 publications
2
3
0
Order By: Relevance
“…The methoxy and allyl carbons gave their characteristic resonances at 55 ppm and 114, 136, and 39 ppm, respectively. 32,33 These results from FT-IR and NMR analyses confirm the formation of the Eu-St Bzo monomer.…”
Section: ■ Results and Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…The methoxy and allyl carbons gave their characteristic resonances at 55 ppm and 114, 136, and 39 ppm, respectively. 32,33 These results from FT-IR and NMR analyses confirm the formation of the Eu-St Bzo monomer.…”
Section: ■ Results and Discussionsupporting
confidence: 59%
“… The 13 C NMR spectrum (Figure S2) gave resonance peaks for oxazine ring carbons at 48 (Ph–CH 2 –N) and 81 ppm (O–CH 2 –N). The methoxy and allyl carbons gave their characteristic resonances at 55 ppm and 114, 136, and 39 ppm, respectively. , These results from FT-IR and NMR analyses confirm the formation of the Eu-St Bzo monomer.…”
Section: Resultssupporting
confidence: 56%
“…The results indicate an improvement in the thermal and mechanical properties and corrosion resistance. The study also concluded that this work can be considered an effective way to use waste products and sustainable biomaterials to develop high-performance hybrid composites [5]. The study dealt with the mechanical properties of epoxy composites that were reinforced with two types of natural waste as a micro filler, with different weight ratios and particle size, pollen 50 µm and sea shells 75 µm.…”
Section: Optimization Of Mechanical Properties Of Recycled Polyuretha...mentioning
confidence: 99%
“…127,128 Besides, it could be doped with fillers to further improve performance. 129 Owing to the limitation of Mannich reaction site in urushiol, one unit phenolic hydroxyl group can be retained, which could promote the ring-opening polymerization of oxazine ring resulting in a lower curing temperature (181 C). In addition, the double bonds in the long chain alkyl group are considered to be simultaneously initiated when the polymerization of oxazine occurs, leading to a resin with excellent toughness and high elongation at break.…”
Section: High Performance Bio-based Benzoxazine Resinmentioning
confidence: 99%
“…Cardanol‐derived benzoxazine could be modified by silicon compounds, the resulting resins are rendered different properties 127,128 . Besides, it could be doped with fillers to further improve performance 129 . Owing to the limitation of Mannich reaction site in urushiol, one unit phenolic hydroxyl group can be retained, which could promote the ring‐opening polymerization of oxazine ring resulting in a lower curing temperature (181 °C).…”
Section: Bio‐based Benzoxazine Resinmentioning
confidence: 99%